Non-Contact Non-Destructive Testing Methods for Large-Scale Carbon Fiber-Reinforced Polymer Aircraft Parts - Daniella B. Deutz; Arnoud F. Bosch; Dion E. Baptista; Erik S. Veen; D. Jacco Platenkamp; H. Patrick Jansen (Engineering Proceedings)
Non-contact NDT methods that can provide fast, automated, in-line quality assurance information on the manufacturing and maintenance of large-scale, thin-walled aircraft parts are necessary for the implementation of thermoplastic CFRP in the next generation of aircraft. Infrared thermography (IRT) is a promising method to fill this gap. Here, the detection of flat bottom holes, inclusions, and interlaminar delaminations in fuselage skin is studied for two types of IRT and compared with ultrasound inspection. Unique to this work are three demonstrations of the potential of IRT to deliver a time-effective, automated inspection approach for large-scale, thin-walled thermoplastic CFRP aircraft parts.